Simultaneous monitoring of the drug release and antitumor effect of a novel drug delivery system-MWCNTs/DOX/TC - Xia Dong; Zhiting Sun; Xiaoxiao Wang; Dunwan Zhu; Lanxia Liu; Xigang Leng (Taylor & Francis Group, 2017)
Monitoring drug release and therapeutic efficacy is crucial for developing drug delivery systems. Our preliminary study demonstrated that, as compared with pristine multiwalled carbon nanotubes (MWCNTs), transactivator of transcription (TAT)-chitosan functionalized MWCNTs (MWCNTs-TC) were a more promising candidate for drug delivery in cancer therapy. In the present study, a MWCNTs/TC-based drug delivery system was developed for an anticancer drug, doxorubicin (DOX). The drug loading and in vitro release profiles, cellular uptake and cytotoxicity were assessed. More importantly, the in vivo drug release and antitumor effect of MWCNTs/DOX/TC were evaluated by noninvasive fluorescence and bioluminescence imaging. It was demonstrated that MWCNTs/DOX/TC can be efficiently taken up by BEL-7402 hepatoma cells. The release of DOX from MWCNTs/DOX/TC was faster under lower pH condition, which was beneficial for intrcellular drug release. The in vivo release process of DOX and antitumor effect in animal model were monitored simultaneously by noninvasive fluorescence and luminescence imaging, which demonstrated the application potential of MWCNTs/DOX/TC for cancer therapy.